Two-dimensional perovskites for photovoltaics. (June 2021) - Fu, W.; Chen, H.; Jen, A.K.-Y.
Abstract: Two-dimensional (2D) perovskites are a new class of promising materials that can complement 3D perovskites for optoelectronic applications owing to their enhanced stability and diverse compositions and properties achieved through proper design of organic spacer cations. However, poor charge transport of 2D perovskites tends to hamper their performance due to the insulating organic spacer cations. This review discusses the key issues which significantly affect the performance of 2D perovskites such as orientation, phase distribution in vertical direction, quantum well distribution, organic spacer cations and device engineering. At the end, the challenges and opportunities for 2D perovskite solar cells are also highlighted. Graphical abstract: Image 1